Implementasi Akuntansi Pertanggungjawaban pada Yayasan Circle Imagine of Society (CIS) Timor di Kota Kupang (Jurnal Kendali Akuntansi, 2025)
This study aims to analyze the implementation of accountability accounting at Circle Imagine of Society (CIS) Timor Foundation in Kupang City. This research uses descriptive qualitative method and examines the implementation of four main elements of responsibility accounting, namely determining responsibility, determining performance measures, assessing performance, and providing rewards and punishments. The results of this study indicate that: (1) Circle of Imagine Society (CIS) Timor Foundation has implemented a clear organizational structure, with a detailed division of tasks for each member, (2) determination of performance measures is based on program effectiveness and operational efficiency, (3) performance assessment of Circle of Imagine Society (CIS) Timor Foundation uses regular standard operating procedures (SOP), (4) Awards are given to members of Circle of Imagine Society (CIS) Timor Foundation who perform well and punishment is given to members of Circle of Imagine Society (CIS) Timor Foundation who violate the code of ethics.